Quality standards and samples in genetic testing - Ravine, David (BMJ Group, 2012)
The most critical performance indicator for medical laboratories is the delivery of accurate test results. In any laboratory, there is always the possibility that random or systematic errors may occur and place human health and welfare at risk. Laboratory quality assurance programmes continue to drive improvements in analytical accuracy. The most rigorously scrutinised data on laboratory errors, which come from transfusion medicine, reveal that the incidence of analytical errors has fallen to levels where most of the residual risk is now found in preanalytical links in the chain from patient to result, particularly activities associated with ordering of tests and sample collection. This insight is important for genetic testing because, like pretransfusion testing of patients with unknown blood groups, a substantial proportion of genotyping results cannot be immediately verified. An increasing number of clinical decisions, associated personal and social choices, and legal outcomes are now influenced by genetic test results in the absence of other confirmatory data. An incorrect test result may lead to unnecessary and irreversible interventions, which may in themselves have associated risks for the patient, inaccurate risk assessment regarding the disease, missed opportunities for disease prevention or even wrongful conviction in a court of law. Unfortunately, there is limited information available about the risk of preanalytical errors associated with, and few published guidelines regarding, sample collection for genetic testing. The growing number and range of important decisions made on the basis of genetic findings warrant a reappraisal of current standards to minimise risks in genetic testing.